Pelatihan Budidaya Maggot dan Produksi Produk Turunannya untuk Mengatasi Permasalahan sampah Organik dan Meningkatkan Minat Kewirausahaan Mahasiswa: The Training of Maggot Cultivation and Derivative Product Production to Address Organic Waste Problems and Increase Student Entrepreneurial Interest - Wulandari, Linda; Runting, Asi Pebrina Cicilia; Yulintine, Yulintine; Norhayani, Norhayani; Limandra, Yulius Triadi; Sitorus, Riki Johan Sunandra; Carolin, Sherra Alicia (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
In Indonesia, waste exceeds landfill capacity, and the volume increases significantly each year. One successful effort to manage organic waste is the cultivation of Black Soldier Fly (BSF). This environmentally friendly entrepreneurial activity addresses organic waste management and increases community income. Maggots, the larvae of BSF, can be utilized and sold as fresh maggots, dried maggots, and derivative products. The involvement of students in the Fisheries Department, Agriculture Faculty, University of Palangka Raya, in entrepreneurial activities remains limited due to several obstacles, including a lack of confidence, a lack of innovative and creative ideas, and the belief that substantial capital is required. However, maggot entrepreneurship doesn’t require much capital because maggot food can be made from organic materials or household waste. Providing training in maggot cultivation and the production of derivative products to students is a breakthrough that enhances their knowledge and skills and helps them explore their entrepreneurial potential. The maggots and the derivative products they produce will have a market value and thus become a source of income. The training evaluation results showed an increase in students’ knowledge and skills in maggot cultivation and the production of derivative products, as well as interest in maggot entrepreneurship. Maggot cultivation not only provides various benefits but also demonstrates their commitment to addressing organic waste issues. Through training and mentoring, students successfully cultivated maggots and produced maggot products, including fresh, dried, and pupae maggots, as well as maggot fertilizer (Frass), and marketed them.